Large-scale dynamic assembly of metal nanostructures in plasmofluidic field. (14th January 2016) - Patra, Partha Pratim; Chikkaraddy, Rohit; Thampi, Sreeja; Tripathi, Ravi P. N.; Kumar, G. V. Pavan
Abstract : We discuss two aspects of the plasmofluidic assembly of plasmonic nanostructures at the metal–fluid interface. First, we experimentally show how three and four spot evanescent-wave excitation can lead to unconventional assembly of plasmonic nanoparticles at the metal–fluid interface. We observed that the pattern of assembly was mainly governed by the plasmon interference pattern at the metal–fluid interface, and further led to interesting dynamic effects within the assembly. The interference patterns were corroborated by 3D finite-difference time-domain simulations. Secondly, we show how anisotropic geometry, such as Ag nanowires, can be assembled and aligned in unstructured and structured plasmofluidic fields. We found that by structuring the metal-film, Ag nanowires can be aligned at the metal–fluid interface with a single evanescent-wave excitation, thus highlighting the prospect of assembling plasmonic circuits in a fluid. An interesting aspect of our method is that we obtain the assembly at locations away from the excitation points, thus leading to remote assembly of nanostructures. The results discussed herein may have implications in realizing a platform for reconfigurable plasmonic metamaterials, and a test-bed to understand the effect of plasmon interference on assembly of nanostructures in fluids.